Web-Based HR Management Information System at the Rio Office, Sepunggur Hamlet, Bathin II Bebeko District, Bungo Regency: Sistem Informasi Pengelolaan SDM Berbasis Web Pada Kantor Rio Dusun Sepunggur Kecamatan Bathin II Bebeko Kabupaten Bungo - Adi Setiawan (International Journal of Technology Vocational Education and Training, 2023)
To increase the effectiveness of handling problems in the community sector, it is essential to overcome Human Resources (HR) management problems. Success in maintaining the integrity of HR information is crucial for allocating aid funds and handling various cases in the community. Therefore, the author developed a web-based PHP and MySQL HR processing information system to ensure practical, efficient and regularly arranged data handling to make retrieval easier. Implementing this information system has significantly impacted supporting the duties and responsibilities of the Rio Dusun Sepunggur Office. However, to increase the benefits of this system, steps are needed, such as further training for users, routine maintenance, regular evaluation of system use, and consideration of integration of functionality with other systems. By taking these steps, the HR processing information system can continue to be a valuable tool in maintaining the effectiveness of services and Human Resource Management at the village level, creating a sustainable positive impact on the community.